Exploring researchers' attitude toward the using of institutional repositories at University Putra Malaysia - Asadi, Shahla; Abdullah, Rusli; Jusoh, Yusmadi Yah; Sidi, Fatimah (Human Resource Management Academic Research Society, 2019)
One of the recent resources used at university libraries is institutional repositories (IRs) which have been considered one of the disseminating and preserving ways for academic research publications. IRs have received considerable attention from researchers across disciplines and around the globe. While that have potentially increased public value, ranking, prestige and visibility of researchers and relevant universities. In this regard, the main aim of this paper is to determine researchers’ attitude concerning the utilization of institutional repositories via a modified Technology Acceptance Model at the University Putra Malaysia (UPM). A structured questionnaire was designed, and a survey was taken using a sample of 90 researchers. The results showed that researchers were aware of the institutional repository and had an attitude an interest of presenting their research to their university repository. They were under the impression that by presenting their research to the institutional repository, their university ranking will increase in addition to the citation impact of their research work.